Effects of two training protocols on the forehand drive performance in tennis - Genevois, C.; Frican, B.; Creveaux, T.; Hautier, C.; Rogowski, I. (The Journal of Strength and Conditioning Research, 2013)
The aim of this study was to examine the effects of 2 training modalities on the tennis forehand drive performance. Forty-four tennis players (mean ± SD: age = 26.9 ± 7.5 years; height = 178.6 ± 6.7 cm; mass = 72.5 ± 8.0 kg; International Tennis Number = 3) were randomly assigned into 3 groups. During 6 weeks, the first group performed handled medicine ball (HMB) throws included in the regular tennis practice, the second group (overweight racket—OWR) played tennis forehand drives with an overweighed racket during the regular tennis practice, and the third group (regular tennis training—RTT) practiced only tennis training as usual. Before and after the 6-week program, velocity and accuracy of tennis crosscourt forehand drives were evaluated in the 3 groups. The main results showed that after 6-week training, the maximal ball velocity was significantly increased in HMB and OWR groups in comparison with RTT (p < 0.001 and p = 0. 001, respectively). The estimated averaged increase in ball velocity was greater in HMB than in OWR (11 vs. 5%, respectively; p = 0.017), but shot accuracy tended to be deteriorated in HMB when compared with OWR and RTT (p = 0.043 and p = 0.027, respectively). The findings of this study highlighted the efficiency of both training modalities to improve tennis forehand drive performance but also suggested that the HMB throws may be incorporated into the preseason program preferably, whereas the OWR forehand drives may be included in the on-season program.